Detection of toxic fluoride ion via chromogenic and fluorogenic sensing. A comprehensive review of the year 2015–2019 - Udhayakumari, Duraisamy (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2020)
Fluoride ion (F−) contamination can be accumulated along the water and the food chain and cause serious risk to public health. It is of the greatest importance that selects the suitable chromophores and fluorophores for the design and synthesis of outstanding selective, sensitive chromogenic and fluorogenic probes for detection of fluoride ion. In this review is mainly focused on the current progress of fluoride ion detection according to their receptors into several categories like anthracene, azo, benzothiazole, BODIPY, calixarene, coumarin, imidazole, diketopyrrolopyrrole, hydrazone, imidazole, naphthalene, naphthalimide, quantum dots, Schiff base and urea group sensing in the year 2015–2019. [Display omitted] •A comprehensive review of chemosensor for fluoride ions from 2015 to 2019•Various fluoride sources, consequences, and adverse health effects are presented.•The selective and sensitive F− ions chemosensors are summarized in detail.•Possible sensing mechanisms in different belongings have been discussed.•The theory involves in the design of sensor for a fluoride ions are covered.